FAKTOR-FAKTIR YANG MEMPENGARUHI MOTIVASI SISWA SEKOLAH DASAR DALAM MENGIKUTI AKTIVITAS PRAMUKA PENGGALANG - Yuliana Yuliana; M. Jaya Adi Putra; Zariul Antosa (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2020)
This article was written based on qualitative research on students' motivation in participating in Boy Scout exercises. This article aims to describe the motivation of students in one integrated Islamic elementary school in Pekanbaru to take part in a scout-raising(penggalang) exercise. The sample in this study were 17 students raising, consisting of 9 men and 8 women. Data was collected using direct interviews with students and documentation in the form of program documents, reports and photos of activities. Held in the even semester term 2019/2020. From the results of data processing it was found that in following the Scouting activities students were influenced by several intrinsic and extrinsic factors. Intrinsic factors are first the need to be accepted and respected, secondly the hope to develop abilities, and thirdly the interests associated with socialization. Next extrinsic factor is the first family, because of the family background of a member of the scout, the second environment, the environment of friendship students become one of the students' encouragement to participate in scout activities, Thirdly the rewards, these rewards are also a bit of one of the reasons children participate in scouting activities , because of the award given by the school to students who excel in scouting activities, triggers the emergence of student motivation. With these results, it is hoped that advanced scout activities will need to consider these three factors.